Cryptocurrency: To regulate or not to regulate? - Zulhuda, Sonny; Sayuti, Afifah (2016)
Cryptocurrency, like Bitcoin, is a digital currency in which encryption techniques are used to regulate the generation of units of currency and verify the transfer of funds, operating independently of a central bank. It is an emerging financial technology enabled by innovation, increasingly popular among global Internet users, and more interestingly, it challenges the existing financial and regulatory rules on the currency and payment systems of the world today. On the other side, certain cryptocurrency like Bitcoin has been actively used as payment tools for illicit transactions. Both the "promising" and "challenging" faces of cryptocurrency triggers causes for concerns for policy makers, not only from financial sector, but also legal and technological sectors. The decentralized nature of cryptocurrency creates unique problems for the government to regulate or impose any regulatory requirements. This paper argues that, in order for Malaysia to remain at the forefront of financial and digital innovation it is timely to look at the question on whether to formulate certain policy and regulatory framework on the use of cryptocurrency in the Malaysian market. The answer can pave the way for Malaysian digital citizens to potentially grab the opportunities made possible by the cryptocurrency technology. For this purpose, the researchers seek to study the features of cryptocurrency and the experiences from policymakers in other jurisdictions in dealing with the matter. Both doctrinal legal research and comparative study will be employed and it is expected that the researcher will recommend certain policy issues for Malaysia to consider.